Manajemen referensi penulisan karya tulis ilmiah Mahasiswa STKIP-PI Makassar - St. Habibah; Syamsurijal Basri; Sumarlin Mus (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This program was driven by the need for studentsand lecturers in utilizing an application tool in order to helpthem at managing the references in the scientific paper. Thepurpose of this training was to provide students of STKIP-PIMakassar in writing scientific papers, especially managingreferences used by using Zotero 5.0 software. The results ofthis training showed that the students and lecturers were veryinteresting to participate in the training as well as using theZotero 5.0 in managing their references. The director ofSTKIP-PI and teaching staff encourage their students to usethe Zotero 5.0 software in writing scientific papers.